How positive emotion shapes the effect of price discounts and E-WOM on online impulsive buying: Evidence from Generation Z - Panasea, I Gede Nandya Oktora; Sawitri, Ni Luh Putu Widya; Darmantara, Made Satria; Suantari, Ni Putu Risky (International research journal of management, IT and social sciences, 2025)
The rapid growth of e-commerce and creative sectors has increased competition for digital-native consumers, especially Generation Z. In this environment, spontaneous online purchases influenced by emotions play a major role in driving sales, yet the processes connecting marketing cues to impulsive online buying are still not well understood. This study explores how positive emotion mediates the effects of price discounts and electronic word of mouth (eWOM) on Gen Z’s online impulsive buying behavior. Data were gathered from 160 Gen Z individuals with prior e-commerce purchasing experience using a structured online questionnaire and purposive sampling. The analysis, conducted through Partial Least Squares Structural Equation Modeling (PLS-SEM), reveals that price discounts significantly influence impulsive online buying both directly and indirectly through positive emotion, indicating partial mediation. Meanwhile, eWOM has no direct impact but affects impulsive buying entirely through positive emotion, showing full mediation. These results emphasize the importance of emotional responses in converting marketing efforts into impulsive purchases. The study enriches online consumer behavior research by linking price incentives and social influence with emotional processes in an emerging market Gen Z setting. Practically, e-commerce platforms should combine compelling discounts with emotionally appealing eWOM to evoke positive emotions and boost impulse buying.